The Biology of Social Adversity Applied to Oral Health. (December 2019) - Gomaa, N.; Tenenbaum, H.; Glogauer, M.; Quiñonez, C.
Biological embodiment is a concept derived from Engel's biopsychosocial model to health, theorized as the process by which adverse social exposures trigger neuroendocrine and immune responses, leading to disease and/or increased disease susceptibility. This critical review discusses the biopsychosocial model as applied to oral health and its relevance to oral health policy while deciphering some of the pathobiological processes underlying social adversity. In periodontal disease, for example, such processes can occur via the activation of the hypothalamic-pituitary-adrenal axis and the consequent release of the chronic stress hormone cortisol. The latter contributes to a proinflammatory immune state that increases the risk for periodontal inflammation. Recent research shows that cortisol relates to an elevated oral inflammatory load, demonstrated as hyperactive neutrophils that are pivotal to periodontal tissue damage. Consistent with the biopsychosocial model, this relationship is amplified in those of lower income and higher financial stress. Similarly, among children from lower socioeconomic backgrounds, cortisol is linked to a higher cariogenic bacterial load. Such findings implicate the stress pathway as key in the oral pathogenic process, particularly under social/socioeconomic adversity. Collectively, this work emphasizes the importance of addressing social factors in alleviating oral disease burden and reducing the social gaps therein.